Pengaruh pengungkapan corporate social responsibility dan financial leverage terhadap cost of equity capital pada perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia pada tahun 2021-2024 - Dheana Revalina Tewu; Herman Karamoy; Steven J. Tangkuman (Manajemen Bisnis dan Keuangan Korporat, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) disclosure and financial leverage on the Cost of Equity Capital (CEC) in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period, using Signaling Theory as its theoretical framework. This study employs a quantitative approach using an associative method and purposive sampling, resulting in a sample of 16 companies with a total of 64 observations during the study period. The data used are secondary data obtained from the companies’ annual reports and sustainability reports. The CSR disclosure variable was measured using the Corporate Social Responsibility Disclosure Index (CSRDI) based on the 2021 Global Reporting Initiative (GRI) standards; financial leverage was measured using the Debt-to-Equity Ratio (DER); and CEC was measured using the Ohlson Model. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 27. The results indicate that CSR disclosure does not have a significant effect on CEC, whereas financial leverage has a positive and significant effect on CEC. An Adjusted R-Square value of 0.066 indicates that these two independent variables account for only 6.6% of the variation in CEC, while the remaining 93.4% is explained by other factors outside the research model. Thus, it can be concluded that financial leverage is proven to be one of the factors influencing CEC, whereas CSR disclosure has not been shown to have a significant effect on CEC among mining companies listed on the IDX during the 2021–2024 period.